Reviewers of the Year. Issue 1 (January 2022) - Simpson, Kathleen Rice
Abstract : Over the past very stressful months (almost 2 years), several reviewers have stepped up and volunteered to review more manuscripts. Others have consistently returned their reviews in a timely manner and included detailed, kind, and helpful information. We are so grateful for our wonderful reviewers that we decided to designate some of them as reviewers of the year for 2021 for service beyond what was expected but very much appreciated.